The Implementation of Asian Value on the Democratic System of Southeast Asia - Rachel Noorajavi (NEGREI: Academic Journal of Law and Governance, 2021)
The dichotomy between the east and the West has become a salient aspect in politics, where people tend to politicize the term to gain power or maintain any other movement. Democracy—as it has been a fascinating long-term issue to discuss—is a state system and the foundation of the establishment of the modern state nowadays. As the concept is constantly developing from time to time, it has been taken as a concern of leaders to implement the democratic ideology in their states—as the voices of people are now becoming the significant consideration in the term of rights where every human deserves the right to speak and right to decide, which apparently comes in the form of democracy. Learning on the condition of current states with the democratic system, sophisticating is to find Southeast Asia with democracy as a prominent actor in the system of the state. Nevertheless, the region has also implemented a value created by the moral and behavioral beliefs of the Asians, namely the Asian value. The value contains a plethora of moral and historical ideologies, and it maintained the establishment of states in Asia for decades since the monarchy era. However, given that there are some biases found due to the dichotomic perceptions between freedom in the democracy and the maintained culture in the Asian value, this study will elicit more on the discussion about these aspects using the method of qualitative literature review